2006
DOI: 10.1093/ecam/nem025
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Using Complementary and Alternative Medicine by Stroke Patients at Two University Hospitals in Korea

Abstract: This study measured the prevalence of complementary and alternative medicine (CAM) use among Korean stroke patients. Questionnaire-based 20-min interviews were conducted at the hospitals by a trained nurse after an outpatient visit. It included questions on demographic information, clinical information and the utilization of CAM. Of 304 stroke-patient respondents, 164 (54%) had used CAM, of which 66% had started taking CAM products following suggestions from family members and other relatives. Of the 57% of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 12 publications
2
38
2
Order By: Relevance
“…Shin reported that 24% of study participants experienced some negative e ects of CAM therapies [16]. e low reporting rate of side e ects in the present study was attributed to the use of prayer rather than herbal products as the most commonly used CAM method in children.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Shin reported that 24% of study participants experienced some negative e ects of CAM therapies [16]. e low reporting rate of side e ects in the present study was attributed to the use of prayer rather than herbal products as the most commonly used CAM method in children.…”
Section: Discussioncontrasting
confidence: 51%
“…erefore, health care professionals must be aware of the e ectiveness, dosages, side-e ects, toxicities and potential drug interactions of CAM modalities. Vitamin use in children is reported to vary between 13% and 24% [7,16]. Ball reported that vitamin use in children with a chronic disease (such as leukemia, asthma, cystic brosis, seizure disorder) varied between 42-100% [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to the results of previous studies assessing the use of CAM. [6,8,17] Only 13.6% of the users had been referred by their physicians in our study. On the other hand, less than half (39.5%) of the users had discussed the use of CAM with their physicians, who were frequently indifferent toward the use of CAM by their patients.…”
Section: Discussionmentioning
confidence: 86%